Experimental Study Of Heat Transfer Rate On Acoustic Liner - Ragupathy, Rohendran (Universiti Sains Malaysia, 2022)
It was originally believed that ice on an aircraft's surface posed a major aerodynamic and flight mechanics problem that could compromise the flight's safety. Hot air jet impingement is one method for eliminating icing from crucial aircraft surfaces, such as the nacelle lip skin. However, the heat transfer rate of the acoustic line which is the material used mainly near the nacelle lip skin has no experimental results so far. The experimental study on the heat transfer rate of the acoustic line is done to determine the heat transfer coefficient of the acoustic liner to better see the process that happens when heat is placed under the acoustic liner and air flow with different velocity is given. 5 different value of heat convection is given for each data set which also has 7 different values of fan velocity for each heat convection value. The acoustic liner is placed on the heater pad and set into a chamber. Thermocouples are place in various spots to measure the ambient temperature, acoustic liner wall temperature and heater temperature. After heating the heater pad for awhile, the fan is switched on and the speed is change every 30 minutes. This is repeated for 7 fan speeds and 5 heat convection values. All test result are somewhat similar to each other. The graph of heat coefficient vs Reynolds number and the graph of nusselts number against Reynolds number multiply by Prandtl number is plotted. Both the graph shows a slight drop before increasing with the Reynolds number also increasing. The slight drop is due to the flow being laminar which is under 2000 reynolds number and transition flow which is around 2000-4000 reynolds number. After reaching a turbulent flow above 4000 reynolds number, the heat transfer increases gradually with the Reynolds number. In conclusion, the acoustic liner serves as a good material for heat transfers as it can work well to reduce ice formation on the nacelle lip skin. The heat transfer rate of the acoustic liner increases with the higher Reynolds number flow.